0441 Attentional Bias Toward Hypnotic-Related Cues in Long-Term Hypnotic Users: An ERP Study. (27th April 2018) - Tu, Y; Lin, Y; Yang, C
Abstract: Introduction: Although hypnotic drugs are often suggested for short-term use, prolonged usage of the hypnotics are common in clinical settings. There has been a concern that whether this practice will lead to drug dependence. Attentional bias to drug-related cues has been indicated as an important factor in substance dependence. This study aims to examine the attentional bias toward hypnotics in long-term hypnotic users by measuring event-related potential (ERP) elicited by hypnotic-related pictures. Methods: 22 insomnia patients were recruited from communities; 13 of them were long-term hypnotic users (> 6 months; LTH group), and 9 of them had not been using hypnotics for 6 months and had never used hypnotics for longer than 3 months (control group). Participants came to the laboratory for a night. An oddball task (20:80) was administered, which included 2 blocks with 32 hypnotic-related or sleep-related (non-target), 96 neutral (non-target), and 32 animal pictures (target) presented on a computer screen in each block. Participants were required to respond to animal pictures as targets. ERPs induced by stimuli were recorded during the task. A polysomnography was conducted afterward to rule out other sleep disorders. The differences of the amplitude and latency of P3 wave, as an index for attentional processing, between groups at Fz, Cz, Pz, F3, F4, C3, C4, P3, P4 channels were evaluated. Results: Both the amplitude and latency of P3 toward hypnotic-related stimuli in LTH group are significantly larger than in control group (amplitude: U=28, p=0.042; and U=25, p=0.025 at F3, C3 channel, respectively; latency: U=29, p=0.049; U=26, p=0.030; and U=24, p=0.021 at Fz, Cz, C4 channel, respectively). There are no significant differences in the amplitude and latency of P3 toward neutral stimuli between two groups. Conclusion: The result shows an enhanced attentional processing toward hypnotic-related stimuli in long-term hypnotic users. The attentional bias toward substance-related cues, which has been shown as a crucial predictor of craving, suggests that there may be an underlying cognitive process associated with substance dependent development in long-term hypnotic use. Support (If Any): Ministry-of-Science-and-Technology, Taiwan (MOST-101-2410-H-004-082-MY3).